Design study of a HPGe detector array for β-decay investigation in laboratory ECR plasmas - Naselli, Eugenia; Santonocito, Domenico; Amaducci, Simone; Celona, Luigi; Galatà, Alessio; Goasduff, Alain; Mauro, Giorgio Sebastiano; Mazzaglia, Maria; Mishra, Bharat; Napoli, Daniel R.; Pidatella, Angelo; Torrisi, Giuseppe; et al. (Frontiers in Physics, 2022)
In the frame of the PANDORA project, a new experimental approach aims at measuring in-plasma β-decay rate as a function of thermodynamical conditions of the environment, namely a laboratory magnetized plasma able to mimic some stellar-like conditions. The decay rates (expected to change dramatically as a function of the ionization state) will be measured as a function of the charge state distribution of the in-plasma ions. The new experimental approach aims at correlating the plasma environment and the decay rate. This can be performed by simultaneously identifying and discriminating—through an innovative multi-diagnostic system working synergically with a γ-ray detection system —the photons emitted by the plasma and γ-rays emitted after the isotope β-decay. In this study, the numerical simulations supporting the design of the γ-ray detector array, including a statistical significance study to check the feasibility of measuring the in-plasma decay rates, are presented. Geant4 simulations focused on the design of the array of γ-ray detectors and the evaluation of total efficiency depending on the detector type and the optimal displacement of detectors around the trap (including collimation systems and shielding). The simulation results showed that, due to technical limitations in the number of apertures that can be created in the magnetic trap, the best compromise is to use 14 HPGe (70% of relative efficiency) detectors surrounding the magnetic trap. The HPGe detectors were chosen for their excellent energy resolution (0.2% @ 1 MeV), since the harsh environment (the background is represented by the intense plasma self-emission) strongly affects the signal-to-background ratio. Once determined the total photopeak efficiency (0.1–0.2%), the sensitivity of the PANDORA experiment was checked in a “virtual experimental run,” by exploring the measurability of isotope decay rates for the first three physical cases of PANDORA: 176Lu, 134Cs and 94Nb. The preliminary results demonstrated the feasibility of the measurement in terms of the signal-to-background ratio and significance that it is possible to reach. The results indicated that experimental run durations could take from several days to 3 months, depending on the isotope under investigation, thus shedding new light on the role of weak interactions in stellar nucleosynthesis.